Strategi Komunikasi Pemasaran dalam Meningkatkan Jumlah Siswa (Studi Kasus pada Bimbingan Belajar Bintang Solusi Mandiri Cabang Pinang, Jakarta) - Saktisyahputra Saktisyahputra (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
Non-formal institutions such as a tutorial should always be ready with the changes issued by the government in the field of education. It should also be ready to compete with other tutorial and schools who offer tutorial services. To the authors chose the title